Artificial Intelligence-Based Health Education to Improve Knowledge and Attitudes toward Hypertension Control in Primary Health Care - Hijrah; Zakariyati; Hasbullah; Reski Apriantih; Mohammad Ardani Samad; Haerah Asrawati (Institut Citra Internasional, 2026)
Hypertension remains a major public health problem that requires effective educational strategies to improve knowledge and attitudes toward disease control. In hypertension education, Artificial Intelligence-based audiovisual media may help translate hypertension-specific messages on risk factors, complications, treatment adherence, lifestyle modification, and blood pressure monitoring into structured, visual, and patient-centered information. This study aimed to determine the effect of Artificial Intelligence-based audiovisual health education on knowledge and attitudes regarding hypertension in the working area of Kassi-Kassi Public Health Center, Makassar. This study used a quantitative pre-experimental design with a one-group pretest-posttest approach. A total of 70 respondents were selected using purposive sampling. Data were collected using knowledge and attitude questionnaires administered before the intervention and seven days after the intervention. The intervention was delivered through a four-minute Artificial Intelligence-based audiovisual video containing information on the definition of hypertension, risk factors, prevention, complications, and management. Data were analyzed using univariate analysis and the Wilcoxon Signed Rank Test. The results showed that the mean knowledge score increased from 36.27 to 44.88, while the mean attitude score increased from 25.51 to 42.24 after the intervention. The Wilcoxon test showed a p-value of 0.000 for both variables, indicating significant differences between pretest and posttest scores. This study concludes that Artificial Intelligence-based audiovisual health education significantly improves knowledge and attitudes regarding hypertension and can be used as a practical educational alternative in primary health care.